“REVELATIONS” IN GIETRZWAŁD AND CONTEMPORARY APPARITIONS OF MARY - Alicja Święcicka (Forum Teologiczne, 2018)
The “Revelations” in Gietrzwałd and contemporary apparitions of Mary is a subject worth analysing, especially so since June 2017 was the 140th anniversary of the Apparitions of Mary in Gietrzwałd. Saint John Paul II perceived the revelations as a sign of the times, upon which the Church shall constantly consider, in order to read them and interpret them anew. The Gietrzwałd “revelations” have much in common with other Marian apparitions, but it is worth noting that every appearance of the Mother of God on Earth is special and unique. There are some differences among the revelations, which suggest a reason for the selection of a given place for Mary’s visit. There is a need to look closely at the apparitions in Gietrzwałd, as this is a site in Poland where the events have been officially recognized by the Catholic Church as true and authentic, but despite that, they are not widely known or valued. The 140th anniversary of those apparitions is a good chance to increase awareness of them, particularly Mary’s widespread wish for us to pray the rosary every day.